PESTNET now for Rwanda - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The African Regional Pest Management R&D Network, better known as PESTNET, has recently finalized the programme and budget for its proposed activities in Rwanda. From the start Rwanda was identified as one of four countries where PESTNET hopes to...